Differential Diagnostic Indicators for the Appointment of Non-Steroidal Anti-Inflammatory Therapy in the Treatment of Red Eye Syndrome at the Stage of Primary Outpatient Admission. Part 1 - V. N. Trubilin; E. G. Poluninа; A. A. Kozhukhov; V. V. Kurenkov; N. V. Moreva; A. V. Trubilin; K. V. Chinenova (Oftalʹmologiâ)
Every practicing ophthalmologist, regardless of the scope of their clinical and scientific interests, is faced with a dilemma — what treatment to prescribe to a patient who applied for a primary outpatient appointment with signs of red eye syndrome? Prescribing an adequate amount of pathogenetically substantiated therapy will reduce the potential risk of developing complications associated with drug therapy.Purpose: to study the effectiveness of the treatment the blepharoconjunctivitis, episcleritis and keratitis, the regimen of which included the non-steroidal anti-inflammatory drug Okofenac 0.09 % (Otisipharm, Russia), the main active component of which is bromfenac, showed that the average term for stopping the inflammatory process in in all groups of patients included in the study, was 7–14 days, which indicates a high level of effectiveness of the treatment. At the same time, the maximum amount of drug therapy — more than two groups of drugs was prescribed to patients with keratitis. The quality of life according to the SPEED questionnaire, which reflects the symptoms characteristic of dry eye syndrome, was significantly lower in patients in the keratitis group, which suggested a relationship between the amount of drug therapy and the onset of dry eye syndrome in the long-term period — 1 month. This assumption was confirmed by a correlation analysis, which revealed a direct correlation between the number of prescribed drugs at the beginning of treatment and the quality of life according to the SPEED questionnaire after 1 month in all three groups of patients included in the study. Since this study was aimed at studying the effectiveness of anti-inflammatory therapy in the treatment of different, not only in terms of pathogenesis, but also the localization of the process, it only revealed certain trends in the relationship between the number of prescribed drugs at the beginning of treatment and the development of dry eye signs in the long-term period. Therefore, further research is needed to study the above trend in detail.In addition, as the analysis of literature data has shown, there are currently no indications for prescribing one or another type of drug therapy in the complex treatment of inflammatory diseases related to the “red eye syndrome”. In order to form criteria that take into account the history data — somatic status, duration of the inflammatory process, complaints of patients characterizing the inflammatory process, as well as biomicroscopic signs of inflammation, to select one or another pharmaceutical group of drugs, a survey of expert ophthalmologists was conducted. Based on the data of the survey, an algorithm for rational therapy of one of the most common pathologies included in the group of diseases red eye syndrome — conjunctivitis was formed. The above algorithm will be presented in the second part of this article.